Case Report: Multiple cutaneous keratoacanthoma-like lesions in a colorectal cancer patient treated with sintilimab - Li, Shiyi; Ye, Xianhui; Li, Xiaofen; Yang, Yu (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors are increasingly being utilized for the treatment of advanced neoplastic disease, and Sintilimab as a selective anti–PD-1 antibody that inhibits interactions between PD-1 and its ligand, is a typical representative of them. Among all the adverse effects(AEs) of sintilimab, skin AEs had affected many people. Though exceedingly rare, eruptive keratoacanthomas-like lesion have been associated with the use of immune checkpoint inhibitors before. Here, we report a case of numerous eruptive keratoacanthoma-like lesions arising in a patient 2 weeks after initiation of sintilimab for rectal adenocarcinoma with liver metastasis. Although eruptive keratoacanthoma-like lesions secondary to sintilimab are exceptionally rarely reported, physicians should be aware of this cutaneous adverse effect as its use becomes more widespread.